2015
DOI: 10.3928/00220124-20150721-03
|View full text |Cite
|
Sign up to set email alerts
|

Use of Workshops to Develop Nurses’ and Nursing Students’ Writing Skills

Abstract: Workshops have been described in the literature as a strategy for preparing nurses to publish their work and develop their writing skills. Articles about the use of workshops for these purposes have not been integrated systematically. Seventeen articles were included in the current review. The workshop method has been found to be effective for preparing nurses to write for publication and for improving nurses' and nursing students' writing skills. However, workshops must be combined with one-to-one mentoring a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…The issue with competing work priorities is difficult to resolve without release time for participants [10]. Derouin et al recommended that clinicians receive incentives such as paid and protected time to attend writing workshops and complete their manuscripts [3]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The issue with competing work priorities is difficult to resolve without release time for participants [10]. Derouin et al recommended that clinicians receive incentives such as paid and protected time to attend writing workshops and complete their manuscripts [3]. …”
Section: Discussionmentioning
confidence: 99%
“…Faculty and health sciences librarians’ efforts to foster writing skills among graduate students, health professions trainees and faculty, and clinicians encompass a variety of strategies. Some of these strategies are intended to develop or improve the individual’s writing skills, such as including writing assignments for students in their academic coursework, writing across the curriculum, holding workshops to help graduate students improve their writing skills, and critiquing scholarly writing by faculty and peers with feedback [13]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though half of this first cohort had previous research experience and all students in SUNRISE had high grade point averages coming into the nursing program and maintain high averages in the BSN program, scientific writing still needs to be developed. In order to address the underperformance in writing skills among nursing students, Derouin et al (2015) found workshops to be effective in preparing nursing students for publications and to improve writing skills. [23] Therefore, to boost their scientific writing skills, a writing workshop will be scheduled during the first weeks of the summer for new cohorts that begin the program.…”
Section: Lessons Learned and Future Directionsmentioning
confidence: 99%
“…In order to address the underperformance in writing skills among nursing students, Derouin et al (2015) found workshops to be effective in preparing nursing students for publications and to improve writing skills. [23] Therefore, to boost their scientific writing skills, a writing workshop will be scheduled during the first weeks of the summer for new cohorts that begin the program. In this workshop, we plan to discuss tips for starting and organizing a paper, American Psychological Association (APA) formatting and citations, tips for better scholarly writing and reviewing common mistakes made in scholarly writing.…”
Section: Lessons Learned and Future Directionsmentioning
confidence: 99%